2013
DOI: 10.1371/journal.pone.0061560
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin1: A Promising Serum Protein Marker for Early Detection of Alzheimer’s Disease

Abstract: Sirtuin (SIRT) pathway has a crucial role in Alzheimer’s disease (AD). The present study evaluated the alterations in serum sirtuin1 (SIRT1) concentration in healthy individuals (young and old) and patients with AD and mild cognitive impairment (MCI). Blood samples were collected from 40 AD and 9 MCI patients as cases and 22 young healthy adults and 22 healthy elderly individuals as controls. Serum SIRT1 was estimated by Surface Plasmon Resonance (SPR), Western Blot and Enzyme Linked Immunosorbent Assay (ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
108
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 23 publications
5
108
0
1
Order By: Relevance
“…levels in young adults among post-graduate students and subjects between 65 and 75 years of age; they found that the serum SIRT1 levels of the elderly subjects were much lower than those of the younger subjects. 22 SIRT1 is an anti-aging factor and has been proven to delay aging.…”
Section: Sirt1 Is Associated With Aging and Inflammationmentioning
confidence: 99%
“…levels in young adults among post-graduate students and subjects between 65 and 75 years of age; they found that the serum SIRT1 levels of the elderly subjects were much lower than those of the younger subjects. 22 SIRT1 is an anti-aging factor and has been proven to delay aging.…”
Section: Sirt1 Is Associated With Aging and Inflammationmentioning
confidence: 99%
“…In general, their role is to maintain cellular functions and promote longevity of the cells in humans as well as other model organisms [147,148]. Sirtuins have been reported to protect the brain from infarction by regulating the blood flow to all parts of the brain, especially the cerebral region [149][150][151]. In normal conditions, SIRT1 has been reported to play a protective role by enhancing the nonamyloidogenic cleavage of amyloid-beta protein (APP) through NFkb inhibition.…”
Section: Hypothetical Mechanism For Cerebral Blood Flow In Admentioning
confidence: 99%
“…In mouse model of AD, Sirt1 reduces tau acetylation thus allowing ubiquitin ligases-mediated degradation of pathogenic phosphorylated tau (p-tau) [94] . A recent study has reported the decline in serum concentration of Sirt1 in AD patients, which provides an opportunity to develop Sirt1 as a predictive marker for AD [95] .…”
Section: Alzheimer's Diseasementioning
confidence: 99%